The role of ethics In finance - Pierre García, Jean (2023)
In light of the persistent number of financial scandals making news and plaguing various organizations, it is reasonable to wonder if there is something intrinsic to either business or the financial system that promotes unethical behavior among those involved in such activities. Codes and tools designed to raise awareness and prevent wrongdoing do not seem to have the desired effect. Does acting morally have the consequence of not generating benefits? This article reviews the proposal of a philosopher, Joseph Heath, who posits that ethical behavior occurs naturally when we ensure the proper functioning of the price system in a competitive market and, therefore, morality would not be something external and strange but rather actually intrinsic to the development of both finance and organizations.